Correlates of antenatal anxiety: smartphone use, depressive symptoms, and hypertensive disorders in a cross-sectional study in Southwest China - Guo, Tianzhi; Yu, Yun; Wang, Xia; Sun, Yuqin; Yang, Chao (Frontiers in Medicine, 2025)
BackgroundAntenatal anxiety is a prevalent yet underrecognized mental health condition with significant consequences for maternal and fetal outcomes. This study aimed to identify psychosocial and behavioral factors independently associated with antenatal anxiety among pregnant women in Southwest China.MethodsWe conducted a retrospective cross-sectional study of 972 pregnant women consecutively attending routine antenatal care at a tertiary hospital in Southwest China (June 2022–June 2023). Eligible participants were ≥18 years with singleton pregnancy; women with pre-existing psychiatric disorders or major fetal anomalies were excluded. Anxiety and depressive symptoms were assessed using the Chinese versions of the GAD-7 and PHQ-9. Clinical, sociodemographic, and smartphone use data were obtained from electronic records and structured assessments. Multivariate logistic regression was used to identify independents of antenatal anxiety (GAD-7 ≥ 10), adjusting for relevant confounders. Model performance was evaluated using ROC curves, calibration plots, and a nomogram.ResultsAntenatal anxiety was present in 51.4% of participants. Independent correlates factors included gestational age (OR = 0.94 per week, p = 0.002), junior high school education or below (OR = 1.81, p = 0.015), hypertensive disorders of pregnancy (OR = 2.06, p = 0.010), smartphone use >4 h/day (OR = 3.01, p < 0.001), nighttime use (OR = 2.26, p < 0.001), social networking as primary use (OR = 1.57, p = 0.013), and PHQ-9 score (OR = 1.31 per point, p < 0.001). The model showed strong predictive accuracy (AUC = 0.803) and good calibration.ConclusionSmartphone overuse, nighttime use, social networking as the primary activity, depressive symptoms, hypertensive disorders, lower education level, and shorter gestational age are significant correlates of antenatal anxiety. Integrating digital behavior monitoring and mental health screening into routine prenatal care may help identify high-risk individuals for early intervention.